Peran Lembaga Perkreditan Desa dalam Pengembangan Kewirausahaan Sosial Masyarakat Bali - I Wayan Ruspendi Junaedi; I Wayan Damayana; Dermawan Waruwu; I Gusti Bagus Rai Utama (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
This study aims to determine the role of the Village Credit Institution (LPD) in increasing social entrepreneurship by conducting interpretive ethnographic research through in-depth interviews with village traditional managers and residents as informants to obtain detailed descriptions of behavior, values ??, and attitudes related to the development of LPD in Bali. The results showed that the LPD has played a role in the development of social entrepreneurship in Balinese in the form of (1) initiating the development of social entrepreneurship; (2) playing a role in the development of social entrepreneurship extracted from the existing social capital in Balinese; (3) increasing a social entrepreneurial spirit in the form of the desire to social values creativity, the existence of economic activities; community empowerment, and resource mobilization; (4) increasing business embryos and social-based business development to increase income and improve family and community welfare. So that suggestions for the community are to maintain the LPD to build social entrepreneurship.